PENGARUH PROMOSI KESEHATAN HYGIENE DAN SANITASI MAKANAN TERHADAP PENGETAHUAN PENJAMAH MAKANAN: Di Kantin Sekolah Tingkat Slta Kabupaten Belitung Tahun 2020 - Monita Hermatuti (2020)
The school canteen is an important infrastructure to fulfill the needs of the school residents. The fulfillment the hygienic food needs is influenced by several factors, these are ingredients, equipment, the food processing and the food handlers. unhygienic food will endanger health and cause diseases such as diarrhea. Research on food handlers in the school canteen shows that food handlers do not yet know how to properly process food. Food handlers in the school canteen still lack knowledge of the application of hygiene and food sanitation. This research purpose for giving health promotion to improve the knowledge about hygiene and food sanitation of food handlers in the senior high school canteen of Belitung Regency on 2020. This research uses a pre-experimental research design with research samples. Data analysis used univariate and bivariate analysis with the Wilcoxon Test at a 95% confidence level (α = 0,05). Bivariate test results obtained on individual hygiene knowledge and food sanitation knowledge that is obtained P-value of 0,000 which means there is an influence of health promotion on knowledge about food handlers food hygiene and sanitation. Suggestions need to follow up in the form of application in food management practices. Keywords: school canteen, hygiene, sanitation, food